Malaysia’s policy towards its 1963 - 2008 territorial disputes. - Salleh, Asri; Che Mohd Razali, Che Hamdan; Jusoff, Kamaruzaman (Academic Journals, 2009)
Malaysia has a number of territorial disputes such as Sipadan-Ligitan, Batu Puteh, Limbang and the Spratly Islands. So far, it had settled two of the disputes through the International Court of Justice (ICJ) that is Sipadan-Ligitan and Batu Puteh Islands. Other disputes remain outstanding and/or unsettled that is the Spratly Islands and Limbang. This paper provides an overview of the disputes and Malaysia’s approaches to manage and/or settle them. As such, it analyzes the factors that influence Malaysia’s policy in this regard. Analysis of the factors suggests that Malaysia’s policy towards territorial disputes has been mainly shaped by the Prime Minister’s Department. Other key foreign policy bureaucracies, such as the Defense and Foreign Ministries, have also been found to play an instrumental role especially through the National Security Council of which the two ministries are part of the other important bureaucracies include ISIS and MIMA. It also suggests that Malaysia’s policy has adopted a pragmatic stature in which it allows for a combination of approaches to settle the disputes. This includes unilateralist approach as in Swallow Reef case, multilateralist as in Amboyna Cay case and bilateralist as in Sipadan and Batu Puteh cases. Finally, based on the analysis, this paper suggests several recommendations with regard to Malaysia’s handling of the territorial disputes.